Online Courses As a Form of Professional Development: Russian Local University Teachers' Experiences - Mitrukhina, Svetlana Vladimirovna (KnE Social Sciences, 2021)
Modern education is a phenomenon that combines offline education (traditional, classroom education) and online education (innovative, distance education), and in recent years its second form has become widespread that it is perceived as a direct threat to the existence of the first one. In a social, scientific and teachers’ field an ambiguous attitude towards online education phenomenon has developed, educational researchers study both positive characteristics of distant education (massiveness, accessibility, various areas, an opportunity to study at any time in any place) and circumstances suggesting some vigilance towards this form of education (not suitable for developing practical skills, there is no precise contact, a low number of students finish courses). Online education is a popular form of modern distance education, implemented through massive open and massive closed educational courses, that is, online courses of specific universities which are placed on world and domestic educational platforms. If, regarding the training of young people (students) through online technologies, the debate about the appropriateness and effectiveness of this form does not subside, then for teachers and university leadership (especially a provincial), online courses are almost a panacea for solving the problem of advanced training. In this research online courses are studied as a form of a university teacher’s professional development. Informal interviews with professors’ Khakas State University named after N.F. Katanov, who had an online course experience, were conducted. The study has revealed the reasons teachers’ satisfaction of this form of this education form and some aspects of their positive and negative experience, etc. Keywords: distant education, online learning, online courses, massive open online courses, mass closed online courses